"Solvent-induced chirality switching" in the enantioseparation of chlorine-substituted tropic acids via diastereomeric salt formation by (1R, 2S)-(−)-2-amino-1, 2-diphenylethanol (ADPE). (26th February 2022) - Chandrasekaran, Srinivas; Hirose, Takuji; Kodama, Koichi
Abstract: The optical resolution of chlorine-substituted tropic acids (TAs) by diastereomeric salt formation with (1 R, 2 S )-(−)-2-amino-1, 2-diphenylethanol ((−)-ADPE) has been demonstrated. Efficient solvent-induced chirality switching was observed in the case of racemic 2-chlorotropic acid ( rac -2-Cl-TA). The recrystallization of the diastereomeric salts of rac -2-Cl-TA from branched alcohols such as i -PrOH and s -BuOH afforded ( R )-2-Cl-TA, whereas ( S )-2-Cl-TA was obtained from linear alcohols such as MeOH, EtOH, and n -PrOH. The chirality switching mechanism was elucidated from the crystal structures of the diastereomeric salts, which revealed that the incorporation of solvent in the ( S )-2-Cl-TA salt crystals played a key role in chirality switching by reinforcing the supramolecular structure of the salt. However, no chirality switching was achieved for racemic 3-chlorotropic acid and 4-chlorotropic acid. The position of the chlorine substituent plays an important role in the solvent-induced chirality switching effect. Graphical abstract: Image 1